Teachers professional upgrading and development at Lebowa In- Service Training Centre: Is the college succeeding in its own terms, as well as in terms of the community in achieving its goal - Seale, Kgaka Moses (My University, 2014)
The study sought to participate in an ongoing debate between state off dais and the community concerning INSET provision at Lebowa In-Service Training Centre, an INSET institution in the former Lebowa homeland. This was done in order to find out how far the College succeeded in upgrading teachers professional qualifications in its own terms, as well as in terms of the community. Data for this study was collected both at the College and in the community. At the College, data was collected from the state documents. Structured interviews were held with the Rector and two Heads of Departments at the College, to find (i) who was admitted/ not admitted to the College, (ii) courses offered, and (iii) their duration. College personnel views were sought concerning the College provision to find their perspective on its provision, and how the College addressed community needs. From the community data was collected through questionnaires which were distributed, completed and collected from a convenience sample made up of ten teachers who trained at the College between 1988 and 1993, five principals who employed these teachers before and after their training at the College and five community leaders who had credibility in the community. They were selected because they were interested, knowledgeable and willing to participate. Data was also collected through interviews to follow-up crucial issues raised in the questionnaires. This data was collected in order to find out from the community (i) which teachers should be admitted at the College, (ii) what courses should be offered, and (iii) their duration. Matches and mismatches between the College provision and community perspectives regarding INSET provision at the College were sought. The findings showed that the College was upgrading M+2 to achieve M+3 qualification, on the one hand. The community on the other hand, indicated that the College was not addressing the issue of under-qualification, that is, upgrading teachers with qualifications below M+2 and thus it did not fully address community needs. A second finding was that the community maintained that the College was not addressing their needs by offering School Library and Media Science course to teachers as there are no libraries in schools in their community, but suggested that the College should offer RDP “target subject” like, English, Mathematics, and Natural Science as long courses. Further findings sho wed that the community wanted the College to offer short courses, such as, Agriculture, Motor Mechanics, and Auto Electrician to address the community needs. The conclusion drawn from the study is that the College succeeds in upgrading M+2 qualification but fails to address the underqualification issue, that of, qualifications below M+2, meaning qualifications such as M+l and /or standard 8 plus Primary Teachers’ Certificate held by teachers who are regarded as unqualified teachers.